Obstructive sleep apnea is associated with increased arterial stiffness in severe obesity. (15th April 2014) - Seetho, Ian W.; Parker, Robert J.; Craig, Sonya; Duffy, Nick; Hardy, Kevin J.; Wilding, John P. H.
Summary Obstructive sleep apnea is associated with obesity and metabolic syndrome, leading to greater cardiovascular risk. Severely obese patients with obstructive sleep apnea may still be at risk of adverse health outcomes, even without previous cardiovascular disease. Pulse wave analysis non‐invasively measures peripheral pulse waveforms and derives measures of haemodynamic status, including arterial stiffness, augmentation pressure and subendocardial viability ratio. We hypothesized that the presence of obstructive sleep apnea in severe obesity, even in the absence of an antecedent history of cardiovascular disease, would affect measurements derived from pulse wave analysis. Seventy‐two severely obese adult subjects [obstructive sleep apnea 47 (body mass index 42 ± 7 kg m−2), without obstructive sleep apnea (non‐OSA) 25 (body mass index 40 ± 5 kg m−2)] were characterised using anthropometric, respiratory and cardio‐metabolic parameters. Groups were similar in age, body mass index and gender. More subjects with obstructive sleep apnea had metabolic syndrome [obstructive sleep apnea 60%, without obstructive sleep apnea (non‐OSA) 12%]. Those with obstructive sleep apnea had greater arterial stiffness, augmentation pressure and decreased subendocardial viability ratio (all P < 0.001), with significantly higher systolic (P = 0.003), diastolic (P = 0.04) and mean arterial pressures (P = 0.004) than patients without obstructive sleep apnea (non‐OSA). Arterial stiffness correlated with mean arterial blood pressure (P = 0.003) and obstructive sleep apnea severity (apnea–hypopnea index; P < 0.001). apnea–hypopnea index significantly predicted arterial stiffness in multiple regression analysis, but components of the metabolic syndrome did not. Thus, patients with obstructive sleep apnea with severe obesity have increased arterial stiffness that may potentially influence cardiovascular risk independently of metabolic abnormalities. The presence of obstructive sleep apnea in severe obesity identifies a group at high cardiovascular risk; clinicians should ensure that risk factors are managed appropriately in this group whether or not treatment of obstructive sleep apnea is offered or accepted by patients.